Collaborative Governance In Public Service In Indonesia: A Systematic Mapping Study - Cahyoko Edi Tando; Sudarmo Sudarmo; Rina Herlina Haryanti (Faculty of Social and Political Sciences, Universitas Diponegoro, 2019)
This research raises a problem in Indonesia’s public services, with its relation to the scope of Public Administration Science. The study aims to analyze research articles in international journals with a time span from 2015 to 2019. The databases that the researchers used in the preparation of these scientific articles are Scopus and Taylor and Francis Group, which already have recognition from academics internationally. This study uses a qualitative research method with a literature review approach model in the form of a systematic mapping study. The research concludes that collaborative governance is most widely applied in public services, especially in the health sector. In addition, the method most commonly used is qualitative research methods with a case study approach